Effect of magnesium fertilization on yield and nutrient status of rice in kole lands - A, Latha; K, Chijina (ORYZA-An International Journal of Rice, 2021)
The field experiments were conducted in farmer's field at five locations each of kole lands to study the effect of Magnesium (Mg) on yield and soil and plant nutrient status of rice during 2012-2013 and 2013-2014. The experiment was laid out in randomized block design with three replications. The treatments comprised of different levels of Mg viz; 40, 60, 80, 100, and 120 kg Magnesium sulphate(MgSO4)/ha along with control. Observations on growth characters yield attributes, yield and soil and plant nutrient status were recorded.Â  The results revealed that application of 100 kg MgSO4 / ha recorded the maximum number of panicles/m2 (419.13), number of grains/panicle (109.36), thousand grain weight (28.78 g), grain (9.27 t/ha) and straw yield (9.04 t/ha) of rice.Â  The results of pooled data on plant and soil nutrient status revealed that application of magnesium had a positive effect on nutrient content and availability of nutrients in soil. A significant positive correlation was also noticed between Mg application, yield attributes, yield and nutrient contents. The study concluded that application of 100 kg MgSO4 / ha was found to be optimum for correcting the deficiency in Mg deficient areas of kole lands under below sea level farming.